TCR-engineered adoptive cell therapy effectively treats intracranial murine glioblastoma. Issue 2 (20th February 2023) - Schaettler, Maximilian O; Desai, Rupen; Wang, Anthony Z; Livingstone, Alexandra J; Kobayashi, Dale K; Coxon, Andrew T; Bowman-Kirigin, Jay A; Liu, Connor J; Li, Mao; Bender, Diane E; White, Michael J; Kranz, David M; et al.
Abstract : Background: Adoptive cellular therapies with chimeric antigen receptor T cells have revolutionized the treatment of some malignancies but have shown limited efficacy in solid tumors such as glioblastoma and face a scarcity of safe therapeutic targets. As an alternative, T cell receptor (TCR)–engineered cellular therapy against tumor-specific neoantigens has generated significant excitement, but there exist no preclinical systems to rigorously model this approach in glioblastoma. Methods: We employed single-cell PCR to isolate a TCR specific for the Imp3D81N neoantigen (mImp3) previously identified within the murine glioblastoma model GL261. This TCR was used to generate the Mutant Imp3-Specific TCR TransgenIC (MISTIC) mouse in which all CD8 T cells are specific for mImp3. The therapeutic efficacy of neoantigen-specific T cells was assessed through a model of cellular therapy consisting of the transfer of activated MISTIC T cells and interleukin 2 into lymphodepleted tumor-bearing mice. We employed flow cytometry, single-cell RNA sequencing, and whole-exome and RNA sequencing to examine the factors underlying treatment response. Results: We isolated and characterized the 3×1.1C TCR that displayed a high affinity for mImp3 but no wild-type cross-reactivity. To provide a source of mImp3-specific T cells, we generated the MISTIC mouse. In a model of adoptive cellular therapy, the infusion of activated MISTIC T cells resulted in rapid intratumoral infiltration and profound antitumor effects with long-term cures in a majority of GL261-bearing mice. The subset of mice that did not respond to the adoptive cell therapy showed evidence of retained neoantigen expression but intratumoral MISTIC T cell dysfunction. The efficacy of MISTIC T cell therapy was lost in mice bearing a tumor with heterogeneous mImp3 expression, showcasing the barriers to targeted therapy in polyclonal human tumors. Conclusions: We generated and characterized the first TCR transgenic against an endogenous neoantigen within a preclinical glioma model and demonstrated the therapeutic potential of adoptively transferred neoantigen-specific T cells. The MISTIC mouse provides a powerful novel platform for basic and translational studies of antitumor T-cell responses in glioblastoma.